Phenomenology of Bugis-Makassar Mompreneurs Navigating Digital Loans - Amin, Andi Mustika (Malaqbi Publisher, 2025)
This phenomenological study examines how Bugis–Makassar mother-entrepreneurs (mompreneurs) in South Sulawesi, Indonesia, experience and navigate digital loan services. Using Interpretative Phenomenological Analysis (IPA), the research engaged fifteen mompreneurs through in-depth interviews, participant observation, and digital trace analysis to understand their lived experiences with fintech lending. Findings reveal that digital loans represent a dualistic phenomenon—providing crucial business liquidity while simultaneously generating moral anxiety tied to cultural values of siri' (honor) and familial obligations. Participants developed hybrid financial strategies that blend digital borrowing with traditional networks, while algorithmic systems created generational divides in technological adaptation. The study identifies five key themes: immediate business agility, moral-social anxiety, algorithmic impersonality, gendered household negotiation, and collective digital practices. These findings underscore how fintech adoption is mediated through cultural frameworks and social relationships rather than being a purely technical process. The research contributes to developing culturally responsive fintech policies that recognize moral economies and support women's digital financial inclusion through community-centered design.